2018
DOI: 10.1080/19491034.2018.1454168
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of genomic instability in laminopathies: Replication stress and interferon response

Abstract: Mammalian nuclei are equipped with a framework of intermediate filaments that function as a karyoskeleton. This nuclear scaffold, formed primarily by lamins (A-type and B-type), maintains the spatial and functional organization of the genome and of sub-nuclear compartments. Over the past decade, a body of evidence has highlighted the significance of these structural nuclear proteins in the maintenance of nuclear architecture and mechanical stability, as well as genome function and integrity. The importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 153 publications
(157 reference statements)
1
49
0
Order By: Relevance
“…Importantly, this study demonstrates a robust effect of calcitriol, hormonal active form of vitamin D, repressing the cGAS/STING/IFN response. Although our previous studies showed this effect in HGPS fibroblasts cultured in the presence of calcitriol for a long period of time (≈90 days) when compared to normal fibroblasts, [2,4,6] now we are able to monitor the activation/repression of these pathways over time. In fact, we find that pre-treatment of cells with calcitriol prevents RAD51 loss, replication stress, and activation of cGAS/STING/IFN pathway upon progerin expression.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Importantly, this study demonstrates a robust effect of calcitriol, hormonal active form of vitamin D, repressing the cGAS/STING/IFN response. Although our previous studies showed this effect in HGPS fibroblasts cultured in the presence of calcitriol for a long period of time (≈90 days) when compared to normal fibroblasts, [2,4,6] now we are able to monitor the activation/repression of these pathways over time. In fact, we find that pre-treatment of cells with calcitriol prevents RAD51 loss, replication stress, and activation of cGAS/STING/IFN pathway upon progerin expression.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, changes in the expression of lamins, especially downregulation, have been associated with poor prognosis in many cancers . These data and the role of lamins in the maintenance of genome stability and function provide evidence for lamins functioning as “genome caretakers.” Although many studies support that lamins are important for DNA repair, DNA replication, and telomere biology, the underlying mechanisms remain poorly understood …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also wanted to study the effect of Lmna-exon-4 mutations at the DNA level, since progeroid and striated muscle laminopathies have been associated with high levels of DNA damage [23][24][25][26]. Quantification of DNA damage by staining for H2AX revealed elevated levels of DNA damage in the R249W clone while no signal was detected in the rest of mutants (Null and Delta) or Controls (Figure 8a).…”
Section: High Levels Of Dna Damage Are Associated With R249w Mutationmentioning
confidence: 99%
“…Lamin A and lamin B play a role in DNA replication and influence various cellular mechanisms that maintain genome integrity and consequently innate immune response. Therefore, defects in lamin functioning could indirectly contribute to muscle disorders (Graziano et al 2018).…”
Section: Novel Atypical Mfm-like Subtypesmentioning
confidence: 99%